Analysis on three phase cascaded H-bridge multilevel inverter based on sinusoidal and third harmonic injected pulse width modulation via level shifted and phase shifted modulation technique - A. Shamsul Rahimi A. Subki; Zahariah Manap; Mohd Zaidi Tumari; Aiman Zakwan Jidin; Shahrizal Saat; Amar Faiz Zainal Abidin; Muhammad Salihin Saealal (Institute of Advanced Engineering and Science, 2021)
This work proposes a comparative analysis of sinusoidal and third harmonic injected reference signal modulation accompany with level-shifted PWM technique named as phase disposition (LSPD), phase opposition disposition (LSPOD), and alternate phase opposition disposition (LSAPOD) and phase-shifted PWM technique. Switching pulses from both reference signal and PWM technique have been fed into three phase eleven level cascaded H-bridge multilevel inverter (CHBMLI) fed on a resistive-inductive load with the modulation depth (MD) set to varied from 80% to 100%. For voltage source inverter, total harmonic distortion (THD) content is critical and must be within the allowable range. To prove the feasibility of the reference signal with carrier signal schemes, the entire simulation of the modulation techniques is established and conducted via the Simulink environment. According to the analyzed result, the performance is acceptable in terms of %THDV and %THDI values. Simulation analysis also indicates, at full modulation depth, due to higher fundamental output voltage component produces via the THIPWM modulation technique compared to the SPWM technique, this causes higher %THDV value.